A subgap density of states modeling for the transient characteristics in oxide-based thin-film transistors. (May 2016) - Wang, Weiliang; Khan, Karim; Zhang, Xingye; Qin, Haiming; Jiang, Jun; Miao, Lijing; Jiang, Kemin; Wang, Pengjun; Dai, Mingzhi; Chu, Junhao
Abstract: The modeling of the transient subgap density of states (DOS) for the investigation of trap densities in the oxide-based thin-film transistors is proposed. The study is based on both transient measurements and physical modeling. In history, the subgap DOS modeling of trap densities have been studied according to the static-state current–voltage characteristics or the capacitance–voltage curves. However, the subgap DOS modeling for the transient curves is seldom proposed. In this study, the transient model of subgap DOS is discussed for amorphous In–Ga–Zn–O (a-IGZO) thin films. This model suggests the subgap DOS exhibits a transient behavior with an exponential distribution on the band edge and a Gaussian distribution in the deep gap level. This study could be helpful to understand and optimize the transient electrical properties of a-IGZO TFTs.